State-of-the-art investigation of wind turbine structures founded on soft clay by considering the soil-foundation-structure interaction phenomenon – Optimization of battered RC piles - Gravett, Dewald Z.; Markou, George (My University, 2021)
Nonlinear dynamic modelling of full-scale wind turbine structures and soil-structure interaction considerations using the 3D detailed approach is the most accurate method of investigating the mechanical response of these structures, but not yet feasible due to numerous reasons. The two main numerical problems that do not allow for this type of analysis to be performed, are the numerical instabilities that immerse during the dynamic analysis and the excessive computational demand. This work will present the computational response of a newly developed algorithm that is used herein to perform modal analysis of wind turbine structures for the investigation of soil-foundation-structure interaction phenomenon. An extensive numerical investigation is presented that foresees the performance of modal and pushover analysis on a wind turbine structure that has an 80 m steel tower and is founded on different soil profiles. The 3D detailed models constructed herein consider the effect of soil-foundation-structure interaction by discretizing for the first time the superstructure, pile foundation and soil domains through 8-noded hexahedral elements, achieving maximum modelling accuracy. The soil material properties used in this research work derived from an onsite geotechnical investigation performed for the needs of the WindAfrica project. After validating the ability of the proposed modelling approach to capture the mechanical behaviour of reinforced concrete foundations through the use of experimental data found in the international literature, the optimum inclination of battered piles was studied through an excessive numerical parametric investigation. Based on the numerical findings, the optimum inclination of the battered piles was that of 10 degrees, where the failure of the wind turbine structure was found to be located at the base of the steel tower due to local buckling.
Keywords: Wind turbines; Soil-structure interaction; Battered piles; Pushover analysis; Modal Analysis; Large-scale numerical models